PENGARUH DISIPLIN KERJA, KERJASAMA TIM DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA TOKO SEMBAKO DI DESA PETANDAKAN BULELENG - Sudarnaya, Ketut; Juni Yanti, Ketut Erika (Jurnal Daya Saing, 2024)
This study aims to determine the effect of work discipline, teamwork, and work environment on employee performance. The type of research is quantitative research because it involves numbers and statistical calculation techniques. The population of this research is all grocery store employee in Petandakan Village. The sample selection in this research was used by saturation sampling means all members of the population are the sample in this research. The number of samples in the research obtained was 32 samples. Sources of data used in this study are primary data in the form of questionnaires measured by the Linkert scale and secondary data in the form of books, journals, theses, and other documents. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS version 22 program. The results of this study indicate that (1) work discipline has a positive and significant effect on employee performance, (2) teamwork has a positive and significant effect on employee performance, and (3) work environment has a positive and significant effect on employee performance.